Victims of violence or agents of change? Representations of women in UN peacebuilding discourse. (3rd May 2016) - Shepherd, Laura J.
Abstract: The Women, Peace and Security agenda at the United Nations is the policy architecture that assures the meaningful participation of women in UN peacebuilding and post-conflict reconstruction activities. It is a reasonable expectation that UN entities would leverage WPS principles and priorities to inform gender-responsive peacebuilding and recovery. This paper investigates the imbrication of WPS discourse in the discourse of the UN Peacebuilding Commission. I argue that there has historically been limited integration of the WPS architecture with the UN PBC, but this does not mean that the Commission's activities are not upholding and even enhancing WPS principles and objectives. The opposite is true, and this raises interesting questions about the coherence of the WPS agenda, and the UN as an organisation, in terms of its ability to develop and implement an integrated and holistic gender-sensitive peacebuilding agenda.